A new species of Stelis subgen. Unciferia (Orchidaceae: Pleurothallidinae) from Costa Rica - Rojas Alvarado, Gustavo (2023)
A new species of Stelis recorded in the middle lands of the Tilarán mountain range and the Volcanic Central mountain range of Costa Rica is described based on living material. Distribution map, line drawing and a Lankester Digital Composite Plate of the new species is provided. The new species Stelis luz-marinae belongs to the Stelis subgen. Unciferia and is related to the Stelis segoviensis group, a group of a dozen species distributed from Mexico to Ecuador, but with its highest diversity in Costa Rica and Panama. The new species is compared to its similar species, as Stelis psilantha, S. segoviensis and S. werckleana, but it can be distinguished by its short coflorescences generally as long as the leaf lenght, its rachis with short internodes, and its yellow-brownish flowers with the adaxial edges of the sepals covered by white or brownish trichomes.